2009
DOI: 10.1017/s0952523809990265
|View full text |Cite
|
Sign up to set email alerts
|

Plasticity of fixation in patients with central vision loss

Abstract: The aim of this study was to explore the plasticity of fixation in patients with central vision loss. Most of these patients use preferred retinal loci (PRLs) in the healthy eccentric part of the retina to fixate, but fixation stability and retinal location are not always optimal for best visual performance. This study examined whether fixation stability and a new PRL location can be trained and whether these changes in ocular motor control transfer into better reading performance. Six patients with age-relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
100
0
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(111 citation statements)
references
References 36 publications
7
100
0
4
Order By: Relevance
“…Previous investigators have shown that although MP-1 parameters for fixation may grossly correlate with reading speed, measurements of fixation with the bivariate contour ellipse formula may correlate better. 37,38 Despite this limitation, the fixation quantification method used by the MP-1 microperimeter provides a rapid recording of fixation ability that agrees with previous measurement methods 39 and an accessible method for detecting progressive change in fixation ability. Our results indicate that fixation quality may indeed decline progressively during GA progression, although refinements in methodology and further validation may be necessary to establish this as an outcome measure in GA.…”
Section: Discussionmentioning
confidence: 85%
“…Previous investigators have shown that although MP-1 parameters for fixation may grossly correlate with reading speed, measurements of fixation with the bivariate contour ellipse formula may correlate better. 37,38 Despite this limitation, the fixation quantification method used by the MP-1 microperimeter provides a rapid recording of fixation ability that agrees with previous measurement methods 39 and an accessible method for detecting progressive change in fixation ability. Our results indicate that fixation quality may indeed decline progressively during GA progression, although refinements in methodology and further validation may be necessary to establish this as an outcome measure in GA.…”
Section: Discussionmentioning
confidence: 85%
“…12,14,17,18,26 Another study 30 using MP1 microperimetry in patients with wet or dry AMD found that PRL eccentricity was a predictor of RS. The authors argued that the PRL used by patients during a fixation task is also preferentially used during a reading task or is used at least in some critical periods of the reading process.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has identified several predictors of reading performance in low vision patients, including reading and letter CS, 6,7 the presence of a deep scotoma in the retinal reading area, 5,[8][9][10][11] fixation features (such as eccentricity, usually related to scotoma size), [12][13][14] and fixation stability. [15][16][17] Although microperimetry has increasingly been used in low vision research, 9,10,13,[18][19][20] Micro Perimeter 1 (MP1; Nidek Technologies Inc., Padova, Italy) retinal sensitivity has not been compared with other psychophysical measures as a predictor of reading ability in low vision patients to the best of our knowledge. Moreover, we have recently introduced Reading Explorer (REX) charts to directly measure the effect of reading material contrast on RS, finding that the impact of reduced contrast on reading is undervalued, 7 and we expanded on this finding in a larger, multicenter study.…”
Section: Methods Standard Measurements Of Reading Ability (Minnesotamentioning
confidence: 99%
“…This means that excessive fixation instability is still likely to affect sensitivity estimates. In future studies it would therefore be instructive to see whether children's fixation stability can be improved, either through practice, instruction, reward, or the use of a more engaging fixation target, and whether, as has been found in some adults, 45,46 improvements in fixation stability lead to improvements in estimated visual sensitivities.…”
Section: Sensitivitymentioning
confidence: 99%